Examining the Relationship Between Religious Orientation and Mental Health in Men Committing Domestic Violence Against Women - Aliakbari, Fatemeh; Taghvaei, Davood; Pirani, Zabih (Psychology of Woman Journal, 2023)
Objective: The family serves as a nucleus for affection among its members. However, the occurrence of violence within the family by one member against others disrupts this function. Domestic violence, primarily targeted at women, causes detrimental and irreversible effects on the mental and physical well-being of women. This study investigated the relationship between religious orientation and mental health in men and domestic violence against women.Methods and Materials:  The present study was descriptive-correlational. The method of data collection was field-based, and the statistical population comprised clients of medical centers in Qazvin city. A total of 300 married men were selected through random sampling. The analytical tools used were descriptive statistics indices, analysis of variance, and Pearson correlation coefficient.Findings:  The results showed that subjects with a more internalized religious orientation and higher mental health scores exhibited less violence against women. Furthermore, religious orientation and mental health interact positively with the enactment of violence against women.Conclusion:  Internalizing religion, treating personality disorders, promoting a culture of dialogue among family members, alongside educational initiatives, can penetrate social attitudes that support inequality among members. By reforming and changing these structures, we will also see improvements in the internal environment of families.